ON AUTOMORPHISMS OF THE RELATIVELY FREE GROUPS SATISFYING THE IDENTITY [x^n; y] = 1 - Stepanyan, Sh.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
We prove that if an automorphism j of the relatively free group of the group variety, defined by the identity relation [x^n; y] = 1, acts identically on its center, then j has either infinite or odd order, where n≥ 665 is an arbitrary odd number.